Early and delayed surgical management of the pronator teres syndrome. Selective reinnervation of the anterior interosseous nerve aimed to restore pinch grip among patients with late clinical presentation - Оlexander О. Gatskiy; Ihor B. Tretyak; Vitalii I. Tsymbaliuk; Iaroslav V. Tsymbaliuk; Оlexander S. Lemeshov (Ukrainian Neurosurgical Journal, 2023)
Background. The incidence of pronator teres syndrome (PTS) is low. The misdiagnosis leads to delay in surgical treatment and irreversible changes not only within the median nerve (MN) itself, but within the sensory and muscular apparatus as well.Objective: to compare the outcomes of early and delayed surgical management of PTS; to compare the restoration of the pinch grip (PG) after decompression and reinnervation (nerve transfer, NT) of the anterior interosseous nerve (AIN) vs. decompression of MN alone in late terms of the disease (PTS).Materials and Methods. Six patients with verified PTS were included into the study. Three patients with the history of the disease (HoD) less than 3 mos. received surgical decompression (SD) of MN under standartized methodology alone. Another three patients with the HoD more than 3 mos. received SD of MN, with two of them received simultaneous NT of the branches of the radial or MN to AIN. In all patients sensory and motor deficit (function of "extrinsic"and "intrinsic"muscles), intensity of the neuropathic pain, both pre- and post-surgery have been evaluated according to MRC Scale and VAS, respectively. An ability to reproduce PG, or “OK” sign, with help of the thumb (flexor pollicis longus muscle – FPL) and index finger (deep flexor muscle – FDP2) were evaluated.Results. All patients showed complete relief of the neuropathic pain (VAS0) regardless of the terms of the disease. Three patients with HoD less than 3 mos. showed good recovery of FPL, FDP2 (M4-5) – all patients were able to reproduce "OK" sign. One patient with HoD more than 3 mos. after SD of MN alone showed no recovery of FPL, FDP2 (M0-1). Another two patients with the HoD more than 3 mos. showed good recovery of FPL and FDP2 (M3-4) after NT to AIN. No patient with HoD more than 3 mos. was able to reproduce "OK" sign.Conclusions. Early decompression of MN in PTS cases results in complete relief of the sensory and motor neurologic deficit; late decompression of MN in PTS cases does not lead to relief of the sensory deficit within NCP autonomous area, while the prognosis of the recovery of the median nerve innervated “extrinsic” and “intrinsic” muscles is rather unfavorable; In case of late PTS presentation, NT to AIN allows restoring only a single component ("extrinsics") of the motor functions of the hand which are required for the succesfull reproduction of the pinch grip; In case of late PTS presentation, poor recovery of OP should be expected, hence the succesfull reproduction of the pinch grip due to the thumb hyperadduction would be impossible; carefull interpretation of the clinical, radiological and electophysiological data on the pre-surgical stage could potentially help avoiding the misdiagnosis and improve the outcomes of the surgical treatment in all cases of a single or multilevel MN entrapment.